Long-Term In-Situ Monitoring and Analysis of Terrain in Gas Hydrate Trial Harvesting Area - Chen Cao; Hao Wang; Yongqiang Ge; Wei Wang; Jin Guo; Peng Zhou; Feng Gao; Jiawang Chen (Sensors, 2022)
With the increase in global energy demand, the exploration and development of natural gas hydrate in sea has become a research hotspot in recent years. However, the environmental problems that may be brought about by large-scale harvesting are still concerns. The terrain monitoring of the trial harvesting area can effectively prevent the geological disasters that may be caused by the development of hydrates. Therefore, we have developed a new terrain monitoring device, which can work in the deep sea for a long time. Firstly, the structure of the sensor arrays and bus-type control system of the device are introduced. Secondly, an arc model with an interpolation method is used for reconstruction of the monitored terrain. Thirdly, after the accuracy of the sensing arrays are verified in laboratory, the device was placed in the Shenhu area of the South China Sea for more than 6 months of in-situ monitoring. Finally, we analyzed the data and concluded that the terrain of the monitored area was relatively flat, where the maximum subsidence was 12.3 cm and the maximum uplift was 2.75 cm.